The contribution of Islamic social finance to economic growth in Indonesia - Siswantoro Siswantoro; Ihsanul Ikhwan (Center for Islamic Economics and Development Studies [P3EI], 2023)
Purpose – This study aims to identify the contribution of Islamic social finance (Zakat, Infaq, and Shadaqah or ZIS) to economic growth in Indonesia, both in the long-term and short-term models. Based on previous studies, government expenditure; investment; and trade openness are also included in the model as control variables.Methodology – Annual time series data for 21 years from 2002 to 2022 were analyzed using the Error Correction Model (ECM) approach to determine the long-term and short-term effects of independent variables on economic growth.Findings – The main findings of this study confirm that Islamic social finance (ZIS) is a financial instrument that benefits the economy. ZIS can be an alternative fund for overcoming various problems of the Muslim Ummah and revitalizing the economy, even more so in a country with a majority Muslim population like Indonesia where ZIS instruments such as Zakat are obligatory to be issued to able-bodied Muslims. The study results show that the effect of ZIS on economic growth in Indonesia is felt in the long term, while in the short term, it has no significant impact.Implication – This research provides insight for related parties (especially National Board of Zakat/Badan Amil Zakat Nasional, BAZNAS) further to optimize the potential of ZIS into productive sectors to improve the economy.Originality – Most previous studies used panel data with a limited period to estimate the effect of Islamic social finance on economic growth, while this research utilized time series data with the ECM approach for a longer period.